AlN/AlGaN HEMTs on AlN substrate for stable high‐temperature operation. Issue 3 (1st January 2014) - Yafune, N.; Hashimoto, S.; Akita, K.; Yamamoto, Y.; Tokuda, H.; Kuzuhara, M.
Abstract : An AlN/AlGaN high‐electron‐mobility transistor (HEMT) fabricated on a free‐standing AlN substrate is demonstrated. A metal stack, composed of Zr/Al/Mo/Au, was found to show low contact resistivity for source and drain ohmic contacts. The fabricated AlN/AlGaN HEMT exhibited a maximum drain current of 38 mA/mm with a threshold voltage of −3.4 V. Negligible drain current degradation was observed at temperatures from 300 to 573 K, demonstrating that an AlN/AlGaN approach on an AlN substrate is promising for stable high‐temperature operation.